Law and Economics : Alternative Economic Approaches to Legal and Regulatory Issues. - Oppenheimer, Margaret (Taylor and Francis, 2004)
The economic analysis of legal and regulatory issues need not be limited to the neoclassical economic approach. The expert contributors to this work employ a variety of heterodox legal-economic theories to address a broad range of legal issues. They demonstrate how these various approaches can lead to very different conclusions concerning the role of the law and legal intervention in a wide array of contexts. The schools of thought and methodologies represented here include institutional economics, new institutional economics, socio-economics, social economics, behavioral economics, game theor.